Clinicopathological characteristics and survival outcomes in human papillomavirus independent cervical cancer: a propensity score matched analysis. Issue 5 (24th March 2022) - Li, Danqing; Huang, Shan; Liu, Ke; Qin, Yuankun; Zhang, Ya; Yang, Yingjie
Abstract : Objective: To investigate the clinicopathological characteristics and overall survival in high-risk human papillomavirus (HPV)-independent and HPV-associated cervical cancer. Methods: Patients with cervical cancer hospitalized between September 2015 and December 2019 from the Affiliated Cancer Hospital of Guizhou Medical University were enrolled. First, patients with negative results by HPV primary screening were excluded. Second, the paraffin-embedded tumor tissues from patients with negative results were used for extraction of deoxyribonucleic acid (DNA). The Hybribio K-37 test (PCR and flow-through hybridization for 37 types of HPV) was used to further identify HPV-negative infection status. Finally, 1:4 propensity score matching between high-risk HPV-independent and HPV-associated groups was performed, and the clinicopathological characteristics and overall survival were compared between the two groups. Results: Forty cervical HPV primary screening negative patients were screened of 729 patients (5.5%). Among them, 13 (1.8%) patients who were identified with high-risk HPV-independent cervical cancer after the K-37 test were selected as the study group. There were significant intergroup differences in the distribution of International Federation of Gynecology and Obstetrics (FIGO, 2018) stage (χ 2 =5.825, p=0.016), pathological types (χ 2 =6.910, p=0.009), lymph node metastasis (χ 2 =6.168, p=0.013), and tumor size (χ 2 =5.319, p=0.021). After propensity score matching, 52 patients from the HPV-associated group were selected as the control group. Patients with high-risk HPV-independent cervical cancer had poorer prognosis than those with HPV-associated cervical cancer (median overall survival: 27 vs 29 months, p=0.03; median disease-free survival: 27 vs 29 months, p=0.021). Conclusion: Patients with high-risk HPV-independent cervical cancer more frequently had advanced stage disease, nodal metastasis, larger tumor, and a higher proportion of adenocarcinoma. The prognosis of patients with high-risk HPV-independent cervical cancer was poorer than those with HPV-associated cervical cancer.